2007
DOI: 10.1007/s10530-007-9103-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of competitive dominance in the invasive ability of the Argentine ant (Linepithema humile)

Abstract: To assess the importance of competition in the advance of invasive species, bait stations have been used to determine the dominance hierarchy of a community of native ants in Doñ ana National Park, southern Spain, and the status of the introduced species Linepithema humile (Argentine ant). Some native species, e.g. Cataglyphis floricola or Camponotus pilicornis, seem to be subordinate, i.e. occupy a low position in the competitive hierarchy; some are dominant (e.g. Pheidole pallidula), and others (e.g. Aphaeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 50 publications
(75 reference statements)
0
38
0
Order By: Relevance
“…In studies of antagonistic interactions, variation in aggression has been shown to influence both species co-existence (Frye 1983, Logan 1984, Morrison 1996 and the displacement of native species by exotics (Carpintero and Reyes-Lopez 2008). Thus, if they represent a widespread pattern, our findings suggest that trait-mediated indirect interactions associated with novel mutualisms between invaders and native species could contribute to the success and detrimental impacts of species invasions.…”
Section: Discussionmentioning
confidence: 68%
“…In studies of antagonistic interactions, variation in aggression has been shown to influence both species co-existence (Frye 1983, Logan 1984, Morrison 1996 and the displacement of native species by exotics (Carpintero and Reyes-Lopez 2008). Thus, if they represent a widespread pattern, our findings suggest that trait-mediated indirect interactions associated with novel mutualisms between invaders and native species could contribute to the success and detrimental impacts of species invasions.…”
Section: Discussionmentioning
confidence: 68%
“…The influence of biotic interactions at this scale of analysis was unexpected because we were not testing the effects of the number of species in local assemblages, but rather the number of genera in entire countries. However, although the presence of related taxa may hinder L. humile invasion during its initial stages, there is little evidence that native ants preclude the establishment of populations of the Argentine ant, particularly if the climate is suitable and human pressure on the environment is high (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Indirectly, climate factors affect resource availability to ants as they interfere with primary productivity (Silva et al, 2014). Low resource availability can lead to higher interspecific competition and species exclusion, and is one of the regulating factors of ant communities (Lach, 2005;Carpintero & Reyes-López, 2008).…”
Section: Introductionmentioning
confidence: 99%